Implementação das ações de protensão em programa de grelha equivalente - Garroni, Elker Lucas (2018)
This research studies the prestress effect on structures of flat plate and beams of concrete. The work consisted of coupling a computational subroutine in the already existing platform, the CALCO. Currently the system allows the analysis, calculation of stresses and displacements, of concrete floors through the equivalent grid and was developed by (CASS, 2015). Initially a module was designed that allows the use of curved pretension cables with predefined geometry. To facilitate the introduction of the pre-tensioning efforts the cables can only be applied to the bars of the grid, and the user can create pretension bands. Then the module in question will transform the pretension action into equivalent nodal stresses. In this way, all the isostatic and hyperstatic stresses of the structure can be calculated. Examples are made and compared with existing programs.